Association between serum complements and kidney function in patients with diabetic kidney disease - Liu, Meng-chao; Li, Jia-lin; Wang, Yue-fen; Meng, Yuan; Zheng, Gui-min; Cai, Zhen; Shen, Cun; Wang, Meng-di; Zhu, Xiang-gang; Chen, Yang-zi; Wang, Yu-lin; Zhao, Wen-jing; et al. (Frontiers in Endocrinology, 2023)
Objective: We aimed to explore the association between serum complements and kidney function of diabetic kidney disease (DKD) in Chinese patients.Methods: This is a retrospective study involving 2,441 participants. DKD was diagnosed according to the Kidney Disease: Improving Global Outcomes (KDIGO) categories. Participants were classified as stages G1-G5 by KDIGO glomerular filtration rate (GFR) categories. Effect sizes are expressed as odds ratio (OR) with 95% confidence interval (CI).Results: After balancing age, gender, systolic blood pressure (SBP), hemoglobin A1c (HbA1C), serum triglyceride (TG), and urinary albumin-to-creatinine ratio (UACR) between the G2-G5 and control groups, per 0.1 g/L increment in serum complement C3 was significantly associated with a 27.8% reduced risk of DKD at G5 stage (OR, 95% CI, P: 0.722, 0.616-0.847, <0.001) relative to the G1 stage. Conversely, per 0.1 g/L increment in serum complement C4 was associated with an 83.0-177.6% increased risk of G2-G5 stage (P<0.001). Serum complement C1q was not statistically significant compared to controls at all stages prior to or after propensity score matching.Our results indicate that high concentrations of serum C4 were associated with the significantly elevated risk of kidney function deterioration across all stages, and reduced serum C3 levels with an increased risk of DKD stage G5.